Comparison study on combustion characteristics and emissions of a homogeneous charge compression ignition (HCCI) engine with and without pre-combustion chamber. (August 2015) - Yousefi, Amin; Gharehghani, Ayatallah; Birouk, Madjid
Highlights: Effect of pre-combustion chamber on HCCI combustion engine was investigated. HCCI engine with modified chamber has more advanced SOC together with higher IMEP. Higher level of NO emissions is produced by HCCI combustion with modified chamber. In modified chamber HCCI engine, both CO and HC emissions decreased drastically. Abstract: There is an urgent need to develop new combustion strategies such as homogeneous charge compression ignition (HCCI) mode to meet current and future emissions regulations. In this study, experiments and a coupled AVL-CHEMKIN CFD (computational fluid dynamic) model were adopted to compare combustion phasing, engine performance and emissions in term of equivalence ratio for both HCCI combustion engines with and without pre-combustion chamber to investigate the effect of pre-combustion chamber on HCCI combustion engine. Results revealed that with an equivalence ratio of 0.2, HCCI engine with pre-combustion chamber (comet MK.V) tolerates misfiring process, while HCCI engine without pre-combustion chamber (modified chamber) experiences a complete combustion. HCCI engine with modified chamber has higher combustion pressure, narrower heat release rate (HRR), more advanced start of combustion (SOC) and higher indicated mean effective pressure (IMEP) in comparison with comet MK.V chamber. For equivalence ratios between 0.2 and 0.5, the average increase in IMEPs is 49.3%. Furthermore, HCCI engine with modified chamber generates higher work per kg fuel compared to comet MK.V chamber. While a high level of nitrogen oxide (NOx ) emissions is produced by HCCI combustion with modified chamber, both carbon monoxide (CO) and hydrocarbon (HC) emissions decreased drastically. In terms of combustion phasing, engine performance and emissions, the HCCI engine with modified combustion chamber is preferred at low equivalence ratios ( Φ < 0.3) compared with comet MK.V chamber.